A Frequency Agile Miniaturized Antenna Utilizing Ferroelectric Barium-Strontium-Titanate Capacitors. Issue 1691 (14th October 2014) - Alzahrani, S.; Kalkur, T.S; Song, H.
Abstract: A miniaturized frequency agile multi-band antenna based on BST varactors is presented. The radiation patterns and frequency responses of this antenna are characterized. The measured tunability was 2.1%, 9.1%, and 6.6% for the first, second, and third band respectively. The lowest resonant frequency corresponds to an antenna size of 0.076 λg × 0.076 λg . The size reduction of the antenna was achieved by employing the novel antenna structure and the thin film BST varactors. The measured -3 dB bandwidth was between 3.1% and 7.4% for all bands.